Synthesis and SAR investigation of haemozoin-inhibiting quinazolines active against Plasmodium falciparum - Benjamin, Stefan Jason (Department of Chemistry, 2017)
Malaria is a potentially fatal blood disease with most deaths caused by Plasmodium falciparum. It exists in 95 countries worldwide and puts nearly 3.2 billion people at risk of contracting the disease. Despite recent advances made in malaria eradication and control including by antimalarial drugs (the mainstay of malaria prophylaxis and disease treatment), the need for new antimalarials due to antimalarial drug resistance which is on the rise, means that malaria research remains an extremely important focus. In this study, 21 derivatives of a biologically relevant scaffold, 2,4-diaminoquinazoline, based on hits found by high-throughput screening were rationally designed and synthesised using a three-step procedure. This involved chlorination of benzoylene urea (1), followed by two successive nucleophilic aromatic substitution reactions. The derivatives were purified by conventional methods before being fully characterised by NMR, HRMS and IR spectroscopy. The derivatives were then tested in vitro for β-haematin inhibition (βHI) using a NP-40 based assay and for aqueous solubility using turbidometry. The compounds were also tested for biological antimalarial activities in chloroquine sensitive (NF54) and chloroquine resistant (DD2) parasites. Cytotoxicity was tested in Chinese Hamster Ovarian cells. Of the 21 synthesised quinazoline derivatives 15 were active with IC₅₀ values below 1500 μM for βHI and of the 15, ten compounds were similarly active with IC₅₀s below 1500 nM for antiplasmodial activity. Three compounds, 13 (NF54), 15 (NF54) and 10 (DD2) possessed potent activity below 120 nM against the indicated Plasmodium strains. Resistance and selectivity indices indicated that 2,4-diaminoquinazolines were not cross-resistant with chloroquine (CQ) and possess selective activity against P. falciparum. On the negative side, they possessed poor aqueous solubility, with the majority in the ranges 5-40 μM. In terms of structure-activity relationships (SARs), the analysis showed that 2,4 substitutions to the quinazoline scaffold in the forms of linear alkyl, secondary and less rigid amine groups, appear to diminish or even abolish activity, whereas substituents such as bulkier aromatics and cyclic alkyl groups, activated or inactivated π systems and combinations thereof, improve activity. The results have shown that the 2,4-diaminoquinazoline scaffold exerts their activity in the form of haemozoin inhibition, decreasing haemozoin levels as well as increasing free haem in the malaria parasite at the IC₅₀, much like well-established βHI antimalarial, CQ. Furthermore, the quinazoline scaffold studied has shown excellent potential and scope for optimisation.